Packaging strategies: knowledge outlook on consumer buying behaviour - Lavuri Rambabu; Ramlal Porika (Journal of Industry-University Collaboration, 2020)
Purpose – Packaging is a mantra for encountering a period of immense potential. It keeps on being seen as a key component in the buying decision, and also it is exhibited as a brand communication gadget that goes past the products and can interface with customers in both the physical and virtual forms. The research aspiration is to establish that the speculation of packaging approaches will influence on buyers’ purchasing mode. An attempt has been made to examine and present the results. This research facilitates to discern the perception of consumer in the direction of packaging strategies and to spot the power of packaging factors, elements and strategies of product packaging on purchasing mode of buyers. Design/methodology/approach – Data were collected from 836 respondents from the four major cities of two states in India through structure questionnaire. Every age of the respondents was targeted in the this study to get their perception and buying mode of them, and the analysis was done by using analysis of variance, correlation and regression analysis by using 23.0 version of SPSS. Findings – The consequence of research reveals that media exposures, packaging strategies and elements have better influence on the buyers’ buying mode. Business people must produce innovative bundling designs for their items to market. These allow the keeping and catching the new and existed customers, because packaging has superior influence and also helps in acquiring and retaining the new consumers for their new products. Research limitations/implications – This study being at micro level considered that the city customers may not be similar to the rural customers. Hence, the perception of rural and urban may not be much different. A sample size is 836 drawn from the four major cities of two states in India; therefore, the sample may not represent the whole population of India. Hence, the limitation of generalization will be there. The elicited opinion of consumers may not be reliable all the times, and study considered only some of FMCG products. Originality/value – The study theme is to establish the theory as stated earlier, and it's proved consumers are considering the packaging styles and designs while purchasing the products, which promotes to meet the expectations of the present and potential customers.